Walking the line on police privatization: efficiency, accountability, and court decisions - Rawlins, Pace William; Kwon, Sung-Wook (2016)
This research reviews key issues in the privatization of local police services by discussing economic and political pressures for police privatization and concerns regarding the quality and accountability of privatized police. In particular, the authors explore whether the cost-efficiency sought from police privatization outweighs a critical side effect of a growing confusion regarding police oversight and significant uncertainties in accountability. They analyze court decisions in the US dealing with the question of whether constitutional protections extend to private police conduct. Relevant court decisions suggest that the confusion may grow even worse and local policy makers may need to pay more attention if they decide to privatize police services. - Reproduced.
Keywords: Courts; Judiciary; Accountability; Privatization; Police